Analysis of the Readiness of Students and Teachers in the Implementation of National Assessments at the Integrated Islamic Middle School Lubuk Cemara Tarbiyah Islamiyah Education Foundation - Sari, Devina (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
The research was entitled 'Analysis of reading by students and teachers in conducting assessments at the Islamic Education Institute of Lubbock Simala'. This is because the national evaluation is known to be one of the guidelines of the Ministry of Education and Culture. A culture that aims to improve the quality of education in Indonesia. Through an appropriate national assessment, students are expected to be able to develop their abilities and personality. The state exam replaces the national exam. This is the second year that the national evaluation has been carried out, but according to the results of last year's evaluation, the Islamic Education Foundation Integrated Islamic Education Foundation MTs has not yet achieved the minimum literacy rate. . Computing capabilities. Therefore, there is a gap between the expectations of the Ministry of National Education and the results of our school evaluation, and researchers are interested in conducting research. This research is a type of qualitative research using data analysis techniques with analytical descriptive methods. Data obtained through observation and interviews. A total of 45 subjects and 5 subjects were taken by the national exam. The purpose of this research is to analyze the willingness of teachers and students to carry out national assessments. The data analysis technique used in this study is the Milles & Huberman model, which includes three data analyses: data reduction, data presentation, and result extraction. Therefore, through data analysis it is known that the preparation of teachers and students when carrying out the national assessment includes: Preparing physical and mental health, preparing facilities and infrastructure, preparing students for knowledge development, and even preparing for technical exams. Doing a national assessment, more on this source textSource text needed to get additional translation information Send feedback Side panel